Mengenal Sejarah Kurikulum Nasional Indonesia dan Hubungannya Terhadap Pengembangan Kurikulum Pendidikan Agama Kristen Masa Kini - Ramses Simanjuntak (SANCTUM DOMINE: JURNAL TEOLOGI, 2017)
If we look at the course of our national education curriculum then we see that the government has struggled to bring a curriculum that is in accordance with the context of learning Indonesian society, it is proven through research change of curriculum that has been going on 10 times.In an effort to understand the history of the national education curriculum mentioned above, the author tries to raise a topic that is closely related to the history of the curriculum and its relationship with the curriculum of Christian Education held inChristian theology / religion schools in remote areas of this country.